Factors associated with symptoms of anxiety and depression in five cohorts of community-based older people: the HALCyon (Healthy Ageing across the Life Course) Programme. - Gale, C; Sayer, A; Cooper, C; Dennison, E; Starr, J; Whalley, L; Gallacher, J; Ben-Shlomo, Y; Kuh, D; Hardy, R; Craig, L; Deary, I; et al. (2011)
Symptoms of anxiety and depression are common in older people, but the relative importance of factors operating in early and later life in influencing risk is unclear, particularly in the case of anxiety.